New methods of market research and analysis - Erickson, G. Scott (Cheltenham Edward Elgar Publishing Ltd., 2017)
New Methods of Market Research and Analysis prepares readers for the new reality posed by big data and marketing analytics. While connecting to traditional research approaches such as surveys and focus groups, this book shows how new technologies and new analytical capabilities are rapidly changing the way marketers obtain and process their information. In particular, the prevalence of big data systems always monitoring key performance indicators, trends toward more research using observation or observation and communication together, new technologies such as mobile, apps, geo-locators, and others, as well as the deep analytics allowed by cheap data processing and storage are all covered and placed in context
Big data and marketing analytics -- 2. Exploratory research design -- 3. Descriptive research design -- 4. Casual research design -- 5. Other topics in research and analytics -- 6. Analytics 1: big data -- 7. Analytics 2: marketing and analytics
Includes bibliographical references an index
Keywords: Management of distribution (Marketing); MARKETING; RESEARCH; Marketing research